2021
DOI: 10.1111/cen.14400
|View full text |Cite
|
Sign up to set email alerts
|

National differences in cost analysis of Afirma Genomic sequencing classifier

Abstract: Context Thyroid nodules of indeterminate cytology can be subjected to molecular testing such as the Afirma Genomic Sequencing Classifier (GSC), thereby minimizing the number of unnecessary diagnostic surgeries. Objective This work aimed to evaluate and compare the cost of routine GSC testing of indeterminate thyroid nodules in different countries. Design, Patients and Main Outcome Measures The cost of diagnostic hemithyroidectomy of indeterminate thyroid nodules was calculated by performing a Monte Carlo simul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…The primary goal of the test is to allow patients to avoid unnecessary surgery by ruling out thyroid cancer. A cost-effectiveness modeling study of the Afirma GSC demonstrated overall healthcare cost savings in the United States relative to routine lobectomy, along with the avoidance of potentially unnecessary surgical complications, which was seen in more than 10% of thyroid surgeries in a national study ( 25 , 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…The primary goal of the test is to allow patients to avoid unnecessary surgery by ruling out thyroid cancer. A cost-effectiveness modeling study of the Afirma GSC demonstrated overall healthcare cost savings in the United States relative to routine lobectomy, along with the avoidance of potentially unnecessary surgical complications, which was seen in more than 10% of thyroid surgeries in a national study ( 25 , 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of similar definitions for complication, length of follow‐up and its quality, a simple conclusion that surgery carries high costs or is not cost‐effective, as written in leading reviews, 42–44 should be done with caution, as the studies in which it was based on may have been exposed to substantial bias. Moreover, differences in thyroidectomy costs between countries were shown to considerably affect cost‐analysis considerations in other scenarios 80 …”
Section: Possible Clinical Concerns Regarding Surgical Management Of Gdmentioning
confidence: 99%
“…Moreover, differences in thyroidectomy costs between countries were shown to considerably affect cost-analysis considerations in other scenarios. 80…”
Section: Healthcare Costsmentioning
confidence: 99%